Christmas at Watkins' Home 4315 Burns Avenue, Los Angeles - Watkins, Howard K. (1977)
Front: Christine Watkins, Howard Watkins, Back: Albert Watkins, Rose Watkins, Sharmaine Sepulveda, Larry Sepulveda, Bonnie Sepulveda